Analisis Strategi Portofolio Bisnis Badan Usaha Milik Negara Berbentuk Perseroan Terbuka - , Hotma Gideon ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This study aims to evaluate the position of the public companies of Indonesia State-Owned Enterprises (SOE) in the matrices of strategic business portfolio. The study also aimed to comparing the financial performance of the public companies with the non-public companies within the SOE. Scope of the study is a statistical study on the financial performance of SOE public companies. The study used two types of data, namely primary and secondary data. Primary data were obtained through financial reports and financial observations, while secondary data are compiled from annual reports that are publicly traded, Badan Pusat Statistik Indonesia publications and data from leading competitorâs companies. There are three types of analysis tools